Studi tentang Implementasi Cash Waqf Linked Sukuk (CWLS) di Bank Mega Syariah KCP Iskandar Muda Medan - Zannah, Kharisma (-, 2025)
This study aims to describe the mechanism of waqf fund collection through Cash Waqf Linked Sukuk (CWLS) at Bank Mega Syariah, Iskandar Muda Medan Sub-Branch. It seeks to measure the level of participation of waqifs and the total funds collected, analyze the compliance of the implementation with Sharia regulations, and evaluate the resulting social benefits and challenges encountered. The research employs a qualitative-descriptive method using a case study approach. Data were collected through semi-structured interviews with the General Banking Manager of Bank Mega Syariah, Iskandar Muda Medan Sub-Branch, as well as observations of operational processes. The findings indicate that the Iskandar Muda Sub-Branch actively promotes education and digitalization of the waqf process, enabling participants to contribute starting from a minimum amount of IDR 1 million, with returns guaranteed by the government. The implementation of CWLS aligns with Sharia regulations, including the Waqf Law, Government Regulation No. 42/2006, and DSN-MUI Fatwa No. 137/2020. The collected funds have increased local community participation and supported social programs such as scholarships and micro-business capital assistance